From the development of an open-source energy modelling tool to its application and the creation of communities of practice: The example of OSeMOSYS. (April 2018) - Gardumi, Francesco; Shivakumar, Abhishek; Morrison, Robbie; Taliotis, Constantinos; Broad, Oliver; Beltramo, Agnese; Sridharan, Vignesh; Howells, Mark; Hörsch, Jonas; Niet, Taco; Almulla, Youssef; Ramos, Eunice; et al.
Abstract: In the last decades, energy modelling has supported energy planning by offering insights into the dynamics between energy access, resource use, and sustainable development. Especially in recent years, there has been an attempt to strengthen the science-policy interface and increase the involvement of society in energy planning processes. This has, both in the EU and worldwide, led to the development of open-source and transparent energy modelling practices. This paper describes the role of an open-source energy modelling tool in the energy planning process and highlights its importance for society. Specifically, it describes the existence and characteristics of the relationship between developing an open-source, freely available tool and its application, dissemination and use for policy making. Using the example of the Open Source energy Modelling System (OSeMOSYS), this work focuses on practices that were established within the community and that made the framework's development and application both relevant and scientifically grounded. Highlights: From development of an open-source energy modelling tool to use for policy making. Standardised and transparent process for code development and update. Engagement with the community of developers and users. Application to energy and Climate-Land use-Energy-Water (CLEW) modelling. Use in capacity building activities on tools for sustainable development strategies.